A study on parental perspectives towards childhood fever - Sothinathan, Pavithira; Kumar, Radha (International Journal of Contemporary Pediatrics, 2019)
Background: Parents play an important role in recognizing and treating paediatric fever as well as initiating home treatment. Their knowledge and attitude can greatly influence paediatric fever treatment and parental phobia may at times lead to overtreatment of fever. Objectives of this study was to assess the knowledge, attitudes and practices of parents towards childhood fever. Methods: This cross-sectional observational study was conducted in the Paediatric department at Saveetha Medical College, Chennai. Data collection from parents was done using a questionnaire to study the knowledge, attitude and practices of parents towards fever and its management in children. Data analysis was done using SPSS 16 software. Results: Total 100 parents participated in the study, most of participants were mothers (69%) and 51% were between 20-30 years. 67% parents believed that fever could cause harmful effects like convulsions and delirium whereas 61% parents believed that consumption of large doses of antipyretic is harmful. Majority of parents 87% were aware that vaccinations can cause fever. Around 82% of parents declared that they had sleepless nights whenever their child was febrile. Majority of the parents 95% stated that they confirmed the presence of fever in their child by tactile assessment. About half the parents preferred using injections for reducing fever than oral medications. Conclusions: The study revealed presence of high levels of anxiety in majority of parents highlighting the need for reassurance and counsel ling by health professionals. Since most of the parents relied on tactile assessment for fever, there is a need to educate them about proper use of a thermometer for accurate detection and better assessment of fever.